Uptake and Distribution of Phenanthrene and Pyrene in Roots and Shoots of Wheat (Triticum aestivum L.). (14th February 2022) - Sobhani, Ayyoub; Salehi-Lisar, Seyed Yahya; Motafakkerazad, Rouhollah; Movafeghi, Ali
Abstract: Uptake, translocation and accumulation of phenanthrene and pyrene by wheat were studied under controlled conditions. Seeds were cultivated in perlite containing 300 mg kg −1 of phenanthrene and pyrene separately, and plants were grown hydroponically for 25 days. Sampling was performed every five days, and PAHs concentrations in roots and shoots of plants were determined using high-performance liquid chromatography (HPLC). The results revealed that phenanthrene naturally exists in wheat, and its concentration in roots was higher than that in shoots. Phenanthrene concentration in the roots was increased during the first 10 days and then was decreased until the 25th day, but its concentration in the shoots generally was decreased during the treatment period. In comparison, pyrene concentration was increased in roots and decreased in shoots during the treatment period. Although pyrene had higher uptake rate than phenanthrene in wheat roots, translocation factor of phenanthrene was higher than that of pyrene. According to the obtained results, phenanthrene can be metabolized in wheat especially in the shoots, but pyrene tends to be accumulated in roots.